Perspectives for progress - Assessment of neuroplasticity with strength training - Aagaard, P.; Bojsen-Møller, J.; Lundbye-Jensen, J. (Exercise and Sport Sciences Reviews, 2020)
Including a brief overview of current investigative approaches, the present Perspectives for Progress article offers an overview of potential future experiments in the field of exercise-related neuroplasticity to strength training. It is proposed that the combination of specific experimental approaches and recently developed techniques holds the potential for unraveling spinal and supraspinal mechanisms involved in the adaptation to strength training.